Cauchy problem for the essentially infinite-dimensional heat equation on a surface in a Hilbert space - Bogdanskii, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
It is proved that the Cauchy problem for a simple parabolic equation with essentially infinite-dimensional coefficients on bounded level surfaces of smooth functions in a Hilbert space is uniformly well posed.